Exploring the Financial Leakages in the Classified Hotels in Jordan: A Managerial Perspective. Issue 4 (2nd October 2017) - Alzboun, Nidal; Khawaldah, Hamzah; Allan, Mamoon; Backman, Kenneth
ABSTRACT: The study aimed to provide a better understanding of financial leakages in a sample of classified hotels in Jordan in terms of its reasons, its channels, and potential ways to reduce it from hotel managers' perspective. Eighteen semistructured interviews were conducted with hotel managers. The results showed a high level of awareness regarding financial leakages by hotel managers. Furthermore, the main reasons for financial leakages included: the high cost of energy, the need to import products not produced locally, and the lack of awareness of sustainability practices. The main channels of financial leakages were: importing furniture and electronics, human resources, and food and beverages not produced in Jordan. The study's main suggestions are to reduce financial leakages, especially energy consumption, and to increase trust in local products.